Analisis Kebijakan Pengawasan Terhadap Penyelenggaraan dan Penataan Reklame Di Kota Semarang - Nuzul Eka Prayoga; Yuwato .; Puji Astuti (Journal of Politic and Government Studies, 2017)
Abstract. Rapid growth of advertising in the city of Semarang, arising from the large number of investors who choose advertising media as their promotional tools because of the attractiveness of holding of advertisement is the commercial side of the people of the city of Semarang. Hence to suppress the rapid growth in advertising, to create order, to control Billboard Semarang City Government then have a tool that is applicable local or Perda. Perda who set about organizing the Billboard in the city of Semarang i.e. Perda No. 14 Year 2012 About the Organization of Advertising. Perda No. 14 Year 2012 contains provisions and rules about how the planning and structuring of advertisement, the process of organizing the Billboard, Billboard permitting, and the mechanism of pengawasaan advertising. This research aims to know the process of supervision in the penyelelenggaraan and Setup Billboard in the city of semarang. Methods used in this research is qualitative, i.e. by doing data collection techniques using interviews, observation and study of the literature. Data analysis was performed with data reduction stage, the presentation of data, verification and withdrawal of the conclusion. The objects of research are spatial Agency staff, advertising and Satpol PP penyelengara. The results showed that the process of organizing and structuring of advertisement in Semarang city administered by Dinas Spatial Semarang that mengau in Semarang Perda No. 14 Year 2012. Supervision run against organizing and structuring the Billboard in the city of Semarang by way of preventive, repressive, surveillance process, periodic supervision, supervision, supervision of surprise inherent. Factors that hinder the process of surveillance against organizing and structuring of advertisement is an understanding of and compliance with the makers of advertising against the regulations. It is recommended that surveillance needed the participation of agencies-agencies besides the Department of Spatial and Satpol PP e.g. wards and other Service-related advertising. Keywords : Policy Implementation, Reklame, Supervision